Hubungan Pola Makan dan Antenatal Care Secara Teratur dengan Kejadian Anemia pada Ibu Hamil di Wilayah Kerja Puskesmas Maron - Usvatimah Usvatimah; Tutik Ekasari; Nova Hikmawati (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Anemia in pregnancy is a condition where the hemoglobin (Hb) level in the blood is less than normal and the hemoglobin (Hb) level in the mother has decreased from the normal Hb level, namely 11 g/dI. One of the main and common causes of anemia in pregnant women is a lack of nutrients. Iron in the body is caused by a lack of food sources that contain sufficient iron, but food sources that have low iron content, so that less iron is absorbed. Apart from the lack of food containing iron, routine antenatal care also influences the occurrence of anemia in pregnant women. Effective antenatal care provides a solid foundation for midwives to first assess the needs of pregnant women and families. The aim of this study was to analyze the relationship between diet and regular antenatal care with the incidence of anemia in pregnant women in the working area of the Maron Community Health Center. The design of this study was cross sectional. The population in this study were all pregnant women who were in the working area of the Maron Community Health Center, totaling 79 respondents. The research sample included 44 respondents of pregnant women who were in the working area of the Maron Public Health Center. With random sampling technique. The instruments used were questionnaires and KIA books. The research results show that almost all anemic pregnant women have poor eating patterns and irregular antenatal care. Based on the chi square statistical test, it is known that the P value is 0.000 α 0.05, so HO is rejected and HI is accepted that there is a relationship between diet and antenatal care with anemia in pregnant women in the working area of the Maron Community Health Center. It is hoped that the results of this research can be used to increase insight into health science, especially midwifery, that a good diet and regular antenatal care are very necessary to prevent risks that will occur during childbirth.